Effective Protection Induced by a Monovalent DNA Vaccine against Dengue Virus (DV) Serotype 1 and a Bivalent DNA Vaccine against DV1 and DV2 in Mice - Zheng, Xiaoyan; Chen, Hui; Wang, Ran; Fan, Dongying; Feng, Kaihao; Gao, Na; An, Jing (Frontiers in Cellular and Infection Microbiology, 2017)
Dengue virus (DV) is the causal pathogen of dengue fever, which is one of the most rapidly spread mosquito-borne disease worldwide and has become a severe public health problem. Currently, there is no specific treatment for dengue; thus, a vaccine would be an effective countermeasure to reduce the morbidity and mortality. Although, the chimeric Yellow fever dengue tetravalent vaccine has been approved in some countries, it is still necessary to develop safer, more effective, and less costly vaccines. In this study, a DNA vaccine candidate pVAX1-D1ME expressing the prME protein of DV1 was inoculated in BALB/c mice via intramuscular injection or electroporation, and the immunogenicity and protection were evaluated. Compared with traditional intramuscular injection, administration with 50 μg pVAX1-D1ME via electroporation with three immunizations induced persistent humoral and cellular immune responses and effectively protected mice against lethal DV1 challenge. In addition, immunization with a bivalent vaccine consisting of pVAX1-D1ME and pVAX1-D2ME via electroporation generated a balanced IgG response and neutralizing antibodies against DV1 and DV2 and could protect mice from lethal challenge with DV1 and DV2. This study sheds new light on developing a dengue tetravalent DNA vaccine.